EFSUMB Position Paper: Recommendations for Gastrointestinal Ultrasound (GIUS) in Acute Appendicitis and Diverticulitis - Dirks, Klaus; Calabrese, Emma; Dietrich, Christoph F.; Gilja, Odd Helge; Hausken, Trygve; Higginson, Antony; Hollerweger, Alois; Maconi, Giovanni; Maaser, Christian; Nuernberg, Dieter; Nylund, Kim; Pallotta, Nadia; Ripolles, Tomas; Romanini, Laura; Saftoiu, Adrian; Serra, Carla; Wüstner, Matthias; Sporea, Ioan (Ultraschall in der Medizin - European Journal of Ultrasound, 2019)
An interdisciplinary task force of European experts summarizes the value of gastrointestinal ultrasound (GIUS) in the management of acute appendicitis and diverticulitis. Based on an extensive literature review, clinical recommendations for these highly common diseases in visceral medicine are presented.In patients with acute appendicitis, preoperative sonography has been established as a routine procedure in most European countries for medical and legal reasons. Routine sonography in these patients may reduce the rate of unnecessary surgery by half. The sensitivity, specificity, and accuracy of ultrasound reach values above 90 % and are equivalent to CT and MRI. However, the high operator dependence may be a problem, for example in point-of-care ultrasound in emergency departments. Structured training programs, quality controls and standardized ultrasound reporting should be increasingly implemented.In the case of suspected acute diverticulitis, “ultrasound first” should also be a basic element in the approach to all patients. Sonography can confirm the diagnosis and allows early risk stratification. As treatment strategies have become less aggressive and more tailored to the stage of diverticulitis, accurate staging has become increasingly important. GIUS and CT have proven to have similar sensitivity and specificity. Especially in cases of uncomplicated diverticulitis, GIUS will be the one and only imaging procedure. CT may work as a backup and has particular advantages for diverticulitis located in the distal sigmoid, inflammation deep in the small pelvis and insufficient ultrasound scanning conditions. This step-up approach (ultrasound first and CT only in case of a negative or inconclusive ultrasound result) has proven to yield the best accuracy.
Keywords: appendicitis; diverticulitis; guideline; ultrasound; gastrointestinal tract